Conceptual integration of Islamic culture and values into medical imaging - Zainuddin, Zainul Ibrahim; Sha'ban, Munirah (2016)
Present-day discussions pertaining to Medical imaging safety involving procedural, radiation, cross-infection, Ultrasound and other risks are directed to their manifestations, safety guidelines and professional obligations. There is little to suggest the alignment of Islamic ethico-religious in a domain of a discipline that deals with the preservation and sustaining the quality of life. This dichotomy could distance the Muslim practitioner from the Islamic spiritual awareness, culture and values in ones’ professional environment. The identification of the theories and concepts in the safety domain in Medical imaging enables the alignment and individual tailoring of the various Islamic knowledge to be made to them. A conceptual framework of integration of Islamic perspectives into the safety domain of Medical imaging is presented. The framework aligns that domain to the Islamic worldview, principles and objectives of the Shari’ah (Islamic way of life), the Islamic belief in the concept of retribution and the Islamic value in accepting professional responsibilities within the context of Amanah (trustworthiness), Ihsan (quality) and Fitrah (inherent good). The integration initiative also incorporates the thoughts of Muslim scholars, who rely on Islamic revealed knowledge as the basis of their judgements, and lessons learnt from past Muslim history and civilisation. Muslim practitioners can apply the framework to engage contemporary safety issues that face Medical imaging from Islamic viewpoints. The frame work can provide a direction towards modifying mindsets and perceptions towards a holistic Islamic ethico-religious culture that underlines the promoting, implementing, sustaining and monitoring of safety aspects. Individual tailoring of those perspectives to the cognitive and affective domains within the individual can act both as a deterrent and a motivational tool in limiting risks in Medical imaging. The approach adopted by the framework can be extended to other theoretical domains in Medical imaging.